Peran Modal Sosial Terhadap Kesejahteraan Pelaku Usaha Laundry Rumahan di Kabupaten Jember - Angella Yunita Azarah; Marshanda Sephira Harpy; Rahmasari Dwi Agustina (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research highlights the importance of social capital in the development of home laundry businesses in Jember. Starting from the significant contribution of MSMEs to the Indonesian economy, especially in creating jobs and driving the economy, the focus of this research is the laundry business as a type of service business that continues to grow. The aim of this research is to analyze the factors that influence the welfare of laundry business actors in Jember, as well as how social capital can be used to overcome challenges such as tight competition and limited capital. This research uses a qualitative descriptive approach with data collection methods in the form of in-depth interviews, observation and documentation. The research results show that social capital through customer networks, local partnerships, and response to feedback can improve the performance and desirability of laundry businesses. The implications of this research emphasize the importance of social capital-based strategies in strengthening relationships with customers and local communities to achieve sustainable business success.